2021
DOI: 10.1017/s1744137421000710
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the special issue on institutions and culture in economic contexts

Abstract: The need of further research on the interlink between culture and institutions has been strongly advocated by economists and institutionalists alike. However, bringing together culture and institutions within an organic framework, though, is a non-trivial operation. This is due to the complexity of the synergies between cultural aspects and institutional devices. This special issue attempts to start filling this gap and to build an ad-hoc systemic platform for disseminating such a debate. To this purpose, it b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Institutional rules include formal ones such as laws and regulations and informal ones such as cultural customs ( Casson et al, 2010 ). The new theory of institutional economics believes that formal institutions play a role only when they are recognized by informal institutions, which is an essential factor in the operation of formal institutions ( Andriani and Bruno, 2021 ). Good institutional rules establish a standardized market environment and promote orderly investment trading activities ( Alam et al, 2019 ).…”
Section: Further Analysismentioning
confidence: 99%
“…Institutional rules include formal ones such as laws and regulations and informal ones such as cultural customs ( Casson et al, 2010 ). The new theory of institutional economics believes that formal institutions play a role only when they are recognized by informal institutions, which is an essential factor in the operation of formal institutions ( Andriani and Bruno, 2021 ). Good institutional rules establish a standardized market environment and promote orderly investment trading activities ( Alam et al, 2019 ).…”
Section: Further Analysismentioning
confidence: 99%
“…In addition, women exhibit higher tax morale than men (Fotiadis, 2021). Subsequent studies conducted in 48 countries have confirmed that citizens' compliance with tax regulations depends not only on the quality of formal institutions but may also be culturally determined (Andriani, 2022).…”
Section: Tax Morality In Research Worldwidementioning
confidence: 98%
“…1. Voigt (2018) adopts an incentive-based approach, arguing that culture, to be considered an informal institution, must include a sanctioning mechanism. In our perspective, we include a broader view that encompasses the moral dimension, treating common beliefs and values as essential elements of informal institutions (Andriani and Bruno, 2022). …”
Section: Notesmentioning
confidence: 99%